MPOX IN PAKISTAN: A CALL FOR VIGILANCE AND GLOBAL HEALTH SOLIDARITY - Shaikh, Babar Tasneem; Abdullah, Muhammad Ahmed; Wasif Malik, Muhammad; Salman, Muhammad (Journal of Ayub Medical College Abbottabad, 2026)
Background With 11 cases and one death in 2024, the Mpox virus was by and large under control in Pakistan as the country followed the screening and surveillance guidelines when Mpox was declared a global emergency. The screening of suspected patients is being done across the country, and those showing symptoms are being sent to isolation wards in hospitals to avoid local transmission of the virus. A recent report published on community-based Mpox and sexually transmitted disease surveillance using discarded condoms in the global south presents an innovative approach to disease monitoring that has significant implications for global health security.[i] This new discovery presents another urgency for Pakistan to deal with in a population which has several high-risk groups involved in unsafe sexual practices. The urgency to integrate such surveillance methods into our health system becomes increasingly evident.[ii] This brief narrative explains how Pakistan’s response to Mpox can align with global health security frameworks emphasizing surveillance, capacity building, stigma reduction, and enhanced border vigilance. Wannigama DL, Amarasiri M, Phattharapornjaroen P, Hurst C, Modchang C, Besa JJ, et al. Community-based mpox and sexually transmitted disease surveillance using discarded condoms in the global south. Lancet Infect Dis. 2024 Aug 21; Online First. doi: 10.1016/S1473-3099(24)00514-0. Rauf SA, Aftab A, Hussain T, Hussain R, Dave T, Shah HH. First case of monkeypox in Pakistan: WHO’s response and steps to prevent an outbreak. IJS Glob Health. 2024 Jan 1;7(1): e0381.